2015
DOI: 10.3174/ajnr.a4502
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Modeled Iterative Reconstruction in Low-Tube-Voltage Contrast-Enhanced Neck CT: Evaluation of Objective and Subjective Image Quality

Abstract: BACKGROUND AND PURPOSE: Dose-saving techniques in neck CT cause increased image noise that can be counteracted by iterative reconstruction. Our aim was to evaluate the image quality of advanced modeled iterative reconstruction (ADMIRE) in contrast-enhanced low-tube-voltage neck CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Thus, low-tube voltage scans in combination with IR algorithms allow substantial lower radiation doses while preserving image quality. [11][12][13][20][21][22] Whole body CTA on a third-generation 192-slice dual-source CT using a combination of several dose saving strategies such as automated tube voltage selection (70-to 150-kVp) and Admire resulted in a tube voltage reduction in 75% of all patients, improved image quality, and 19% lower radiation doses compared to second-generation 128-slice dual-source CT. 23 Further, quantitatively improved image quality with, simultaneously, 34% lower radiation doses have been reported for contrast-enhanced venous neck CT when reduced tube voltages of 70-kVp to 90-kVp were used on a third-generation dual-source CT scanner compared to 100-kVp on a second-generation dualsource CT scanner. 24 Our study could show that 90-kVp CTA of the supraaortic vessels demonstrated a mean dose reduction of 40.3%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, low-tube voltage scans in combination with IR algorithms allow substantial lower radiation doses while preserving image quality. [11][12][13][20][21][22] Whole body CTA on a third-generation 192-slice dual-source CT using a combination of several dose saving strategies such as automated tube voltage selection (70-to 150-kVp) and Admire resulted in a tube voltage reduction in 75% of all patients, improved image quality, and 19% lower radiation doses compared to second-generation 128-slice dual-source CT. 23 Further, quantitatively improved image quality with, simultaneously, 34% lower radiation doses have been reported for contrast-enhanced venous neck CT when reduced tube voltages of 70-kVp to 90-kVp were used on a third-generation dual-source CT scanner compared to 100-kVp on a second-generation dualsource CT scanner. 24 Our study could show that 90-kVp CTA of the supraaortic vessels demonstrated a mean dose reduction of 40.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of a steadily improvement of CT hardware and new IR algorithms, prior studies pointed out increased artifacts at the lower neck/shoulder level in venous contrast-enhanced neck CT at 70-kVp scans. 12,27 As CTA scans in the head and neck region are generally scanned with lower tube current settings than venous CT scans, risk of non-diagnostic images due to streak artifacts at shoulder level might be higher and, thus, 70-kVp CTA scans should be used with caution to prevent non-diagnostic examinations. However, application of advanced IR algorithms in 80-kVp cervical CTA and 90-kVp venous neck CT lowered image noise substantially and increased CNR compared to filtered back projection reconstruction, even at shoulder level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ADMIRE algorithm belongs to the category of model-based iterative algorithms, as it implements a statistical model for both the raw projection data and the image data, as well as a system model for the forward projection (7). The ADMIRE algorithm performs detailed modeling in the projection data domain, resulting in less noise and improved artifact suppression (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%